The Effectiveness of Slow Deep Breathing Innovation on Headache in Hypertensive Patients - Ayuni, Anggun; Hardono, Hardono (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective : Hypertension is an increase in blood pressure beyond normal limits, specifically above 140/90 mmHg. The objective of this study was to determine the effect of slow deep breathing relaxation technique on headache in hypertensive patients. Method: This study utilized a case study methodology, focusing on an individual with hypertension at the RPDC of JEND. Ahmad Yani General Hospital, Metro. Data collection tools included a numerical scale and observation sheet. Analgesic administration was conducted after 7 hours of drug administration, carried out over 3 days, with each session lasting 10 minutes. Result: On the first day, the client's pain score was 7 before the intervention and decreased to 6 after the intervention. On the second day, the score was 6 before the intervention and decreased to 4 after the intervention. On the third day, the score was 4 before the intervention and decreased to 2 after the intervention. Conclusion: The results obtained by the author on the third day showed that the patient experienced a reduction in pain, with pain scores of 6 on the first day, 4 on the second day, and 2 on the third day. Additionally, the patient had understood how to perform slow deep breathing correctly.